Portrayal of Love and Romance: a Comparative Analysis of Lahiri’s Interpreter of Melodies and Sidhwa’s Their Language of Love - Dr. Zia Ahmed (University of Chitral Journal of Linguistics and Literature, 2021)
This paper aims to investigate the portrayal of love and its expression in Lahiri and Sidhwa’s short stories and attempts to determine the voice and agency of female expression of love. Love and its expression have been the privilege of male in the narratives emerging from South Asia, and female generally had been unexpressive and maintained silence. But the women of the modern times wish to give agency to their thought and so the fictional narratives from Indo-Pak subcontinent are currently giving voice to the women. This problematizes the socio-political and cultural norms and their working in South Asian societies which necessitates to explore the current narratives. The writers intend to read the selected chunks of short stories by Lahiri and Sidhwa under the lens of postcolonial feminist theory. The stories Interpreter of Melodies (1999), Their Language of Love (2013) by these two writers respectively convey a dominant view of women’s agency of love with the significant impact on social and literary scene. The most probable outcome of research is that the women in 20th century Indo-Pak subcontinent are finding their voice not only represented but are being listened through the narratives from South Asia.